Comparative Analysis of Psychology Responding to COVID-19 Pandemic in Brics Nations - Almondes, Katie Moraes de; Bizarro, Lisiane; Miyazaki, Maria Cristina Oliveira Santos; Soares, Maria Rita Zoéga; Peuker, Ana Carolina; Teodoro, Maycoln; Modesto, João Gabriel; Veraksa, Aleksander N.; Singh, Purnima; Han, Buxin; Sodi, Tholene (Frontiers in Psychology, 2021)
The BRICS Forum, an independent international organization encouraging commercial, political and cultural cooperation between the Brazil, Russia, India, China and South Africa, was formed in 2011 and these countries have significant influence on their regional affairs. These nations were hit by Covid-19 in different times, and all adopted home quarantine to reduce the spread of the virus. We present a comparative analysis of actions of psychology and potential outcomes during Covid-19 pandemic in BRICS nations regarding five aspects: psychology in health policies, social roles of psychology, socioeconomic context, actions for the general population and health professionals during stage 1 of the pandemic, and possible actions in stage 2. Various types of actions were taken by psychologists in BRICS, with different levels of coordinated cooperation with government and non-governmental organizations, multiple and parallel efforts from different scientific societies and professional regulatory agencies. Scientific societies have had an important role on coordinating some of these efforts, especially because they congregate psychologists from different parts of these countries, improving communication and access to key information. The aim of these actions varies from improving situational skills and competences to increase the accessibility of psychological services and provide psychoeducation and telepsychology. We will consider the social importance of these actions within these countries as a global opportunity for psychology to stage in complex context involving human health. The way psychology in BRICS will face this challenging situation is likely to produce important regional influence, stimulate scientific contribution and increase accessibility of psychology.